The influence of age on the effectiveness of neuromuscular training to reduce anterior cruciate ligament injury in female athletes: A meta-analysis - Myer, G. D.; Sugimoto, D.; Hewett, T. E. (Journal of Athletic Training, 2012)
Context: Sports related injuries to the anterior cruciate ligament (ACL) increase during adolescence and peak in incidence during the mid to late teens for females. In response to the evidenced high rates of injuries, neuromuscular training (NMT) programs are often prescribed to reduce the ACL injury incidence in these populations. Longitudinal biomechanical investigations indicate that a potential window of opportunity is present prior to the peak injury incidence, which would be optimal timing for the initiation of integrative NMT in female athletes. However, the influence the timing of initiation of these programs on the efficacy of ACL injury reduction has yet to be evaluated. Objective: To systematically review and synthesize the scientific literature in regards to the influence of age of NMT implementation on the effectiveness for reduction of ACL injury incidence. Data Sources: A computerized search was performed using PubMed, CINHAL, Health source, Medline, SPORT Discus, (1995-2010)in September, 2011. Key words were "anterior cruciate ligament", "ACL", "prospective", "neuromuscular", "training", "female" and "prevention". Language was limited to English. Abstracts and unpublished data were excluded. Study Selection: Criteria for inclusion required that 1)number of ACL injuries were reported, 2)a NMT program was utilized, 3)females were included as participants, 4)studies used pro-spective, controlled trials, and 5)age of the participants to the program was documented or was reported by the corresponding author on follow-up contact. Data Extraction: Number of ACL injuries, the number of subjects and the age of participants for intervention and control groups were extracted. The age of participants (mean or ranged data) were analyzed with dichotomous categorization (.18yrs vs >18yrs) and aggregated into tertiary categories of early adult(>20yrs), late teens(18-20yrs), or mid teens(14-18 yrs).A metaanalysis with odds ratio(OR) was used to compare a ratio of ACL injuries between intervention and control groups among differing age categorizations. Data Synthesis: Eleven of 528 studies were included. Results are presented as OR [95%Confidence Intervals]. The dichotomous analysis demonstrated statistically lower ACL injuries(OR 0.26: [0.16,0.43])in .18yrscompared to >18yrs(OR 0.81: [0.53,1.25]) group. The tertiary analysis indicated statistically lower ACL injuries in youngest age group(OR 0.26: [0.16, 0.43]) compared to late teens(OR 0.48: [0.21,1.07]) and early adult(OR 1.00: [0.59,1.70])participants undergoing NMT. Conclusions: The findings of this meta-analysis revealed an age related association between NMT implementation and reduction of ACL incidence. Both biomechanical and the current epidemiological data indicate that the potential window of opportunity for optimized ACL injury risk reduction may be prior to the onset of neuromuscular deficits and peak knee injury incidence in females. Specifically, it may be optimal to initiate integrative NMT programs during pre-adolescence, prior to the period of altered mechanics that increase injury risk.